Goji berry (Lycium barbarum) inhibits the proliferation, adhesion, and migration of oral cancer cells by inhibiting the ERK, AKT, and CyclinD cell signaling pathways: an in-vitro study [version 1; peer review: 2 approved] - Shama Prasada Kabekkodu; Usha Nayak; Aditi Chopra; Richard Lobo; Ananth Srivatsa; Divya Adiga; Amee Sanghavi; Ashmeet Shah; Shivaprasada Gadag; Karthik Sivaraman (F1000Research, 2022)
Background: Lycium barbarum (L. barbarum), popularly referred to as Goji berry, is a promising herb known for its powerful anti-antioxidant, antibacterial, and anti-inflammatory properties. It is used in traditional Chinese medicine due to its powerful antioxidant, antibacterial, and anti-inflammatory properties. It has also shown good anti-cancer properties and has been tested against liver, colon, prostate, breast, and cervical cancers. However, no study has yet evaluated the role of goji berries against oral cancer. Hence, the present paper aims to evaluate the anticancer properties of L. barbarum against oral squamous cell carcinoma. Method: Ethanolic extract of L. barbarum (EELB) was tested for its anticancer properties by performing the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay, colony formation, cell proliferation, and scratch wound test. The impact of EELB on the signaling transduction pathways of Extracellular signal-regulated kinase (ERK1/2), protein kinase (AKT1), cyclin D1 and epithelial-mesenchymal transition (EMT) was also assessed by western blot. Results: The results showed that EELB can impede CAL-27 cell growth, proliferation and migration in-vitro.. It even reduced the phosphorylation of ERK1/2 and AKT1 with concomitant downregulation of cyclin D1 (CCND1), cadherin 2 (CDH2), and vimentin (VIM) and upregulation of cadherin 1 (CDH1) expression suggesting its anti-proliferative and anti-EMT effects in oral cancer. Conclusion: Goji berry has good antiproliferative and anti-invasive properties. It affects potential EMT markers and signaling transduction pathways involved in oral cancers. Hence goji berry can be tried as a potential anticancer agent to manage oral squamous cell carcinoma.